Pengaruh Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pelanggan - Sustiyatik, Enni (Universitas Hang Tuah, 2020)
The purpose of this study was to test and analyze the effect simultaneously and partially the effect of service quality and promotion on customer satisfaction at Kedai Expo Kediri. This type of research is an associative study which explains the relationship and influence between the Influence of Service Quality and Promotion variables on Customer Satisfaction. The population in this study amounted to 8000 visitors. The sample criteria are respondents who have visited Kedai Expo, respondents who have made purchases at Kedai Expo Kediri. The sampling technique in this study was conducted using purposive sampling. The sample size was performed using the Slovin technique. From a population of 8000, with Slovin calculations the number of samples is 100 people. Data were analyzed using Multiple Linear Regression. Based on the results of the research and data analysis it was concluded that; (1) Simultaneously, Service Quality and Promotion variables affect Customer Satisfaction. (2) based on the partial t test, the variable of Service Quality and Promotion has an effect on Customer Satisfaction.